Evaluation of a biocompatible sealant for on-demand repair of vascular defects—a chronic study in a large animal model. (11th March 2020) - Wussler, Desiree; Kiefer, Selina; Naumann, Susanne; Hackner, Danilo; Nadjiri, Jonathan; Meckel, Stephan; Haberstroh, Jörg; Kubicki, Rouven; Seifert, Andreas; Siepe, Matthias; Ewert, Peter; Stiller, Brigitte; et al.
Abstract: OBJECTIVES: Existing surgical sealants fail to combine design requirements, such as sealing performance, on-demand activation and biocompatibility. The aim of this study was to compare the effectiveness and safety of the SETALIUM™ Vascular Sealant (SVS), a novel, on-demand activatable sealant, with the commercial sealant, BioGlue ®, for the repair of vascular defects. METHODS: In an in vivo porcine model, the use of SVS was compared with BioGlue, for sealing 2-mm defects of the carotid artery and jugular vein. Animals were followed for 7 days and 5 weeks (each time point and per experimental group, n  = 4), respectively. The degree of stenosis and flow velocity was determined, and the local tissue response was evaluated. RESULTS: In vivo incision closure succeeded in all cases, and SVS was superior in clinical usability, enabled by its on-demand activation. Unlike BioGlue, SVS use did not induce stenosis and was associated with physiological blood flow in all cases. Moreover, closure with SVS was associated with a low inflammatory reaction and no thrombus formation or intima proliferation, in contrast to BioGlue. CONCLUSIONS: SVS demonstrated effective and rapid sealing of 2-mm vascular defects, with favourable biocompatibility compared to BioGlue. Thus, SVS seems to be an effective and safe vascular sealant.